Dilemma in Classifying Tasks Performed for the Protection of the Civility (Civil Defense) in Time of War - Wojciszko, Mariusz (Roczniki Nauk Społecznych, 2026)
A review of Poland’s national security and defense strategies to date makes it possible to get acquainted with the official main directions of the activities of the non-military part of the state defense system. These include ensuring in the event of an external military threat and war: support of own troops and allied troops conducting a defensive operation on the territory of the Republic of Poland; continuity of the functioning of state structures; living conditions and survival of the civilian population. Such a presentation of the functions of the non-military subsystem of the of the state defense system, situates the tasks for ensuring living conditions and survival of the civilian population in the category of defense tasks. Therefore, it is worth posing the question of whether the tasks for ensuring the livelihood and survival of the civilian population fall within the strictly defense sphere, within which defense tasks are identified?